The theme of tribulation as a literary strategy of an alternative self-definition in the book of revelation: a sociolinguistic perspective - Nogwina, E. M. (Department of Religious Studies, 2023)
This study focuses on the significance of the theme of tribulation as developed by the author of the Book of Revelation. Its main concern is to examine what the author wants to achieve by depicting the tribulation of his audience. As such, the emphasis is on the social function of the notion of tribulation within the context of the social environment shared by the author and his audience. The methodology adopted here is that of a sociolinguistic perspective. This approach is based on the premise that language both provides information about the social context in which it is used and serves certain functions in the process of social interaction within that context. Within the wider perspective of sociolinguistics, the model that is used here is that of Antilanguage An antilanguage is a language that is generated by an antisociety, that is, a social collectivity which is embedded in another society but feels threatened or alienated by the dominant conventional norms of the wider society, and therefore sees itself as a conscious alternative to it. The language generated by such a social collectivity serves to express its alternative view of social reality and becomes a mode of resistance to the prevailing social order. This study proposes that the author of Revelation assumes that his audience constitutes an antisociety. Therefore, through the language that he uses to depict what he considers to be a state of tribulation for his audience, the author is engaged in the discourse of anti language. This provides the author with both a mode of resistance to the dominant social system and an alternative framework in terms of which his audience can understand and define themselves, relative to the wider society. To arrive at the above conclusion, however, it has become essential to delineate the scenarios proper to the social environment shared by the author and his audience. It has been noted that the tribulation addressed by the author of Revelation is a complex phenomenon in which various elements and forms of social conflicts coalesce. Such conflicts emanate from everyday interaction with other social groups such as the Roman authorities, Jews, Gentile neighbours and Christian rivals. From the perspective of the author of Revelation, however, the ultimate source of the alienation of his audience is the social system promoted and dominated by imperial Rome, imperial cult. antilanguage is particularly as it manifests itself through the Therefore, the actual target of the author's the imperial world view expressed through the practices associated with the imperial cult.